Implemented and perceived high-performance work system and its effect on branch performance: A 2-1-2 mediational multilevel approach. Issue 4 (6th June 2019) - Ali, Muhammad; Lei, Shen; Freeman, Susan; Khan, Mubbsher Munawar
Abstract : Purpose: The purpose of this paper is to examine the influence of high-performance work systems (HPWS) on unit performance relative to the mediating roles of collective human capital (CHC) at the unit level and perceived HPWS at the employee level. Design/methodology/approach: Data were collected from 181 branch managers and 504 employees. The proposed path model was tested using the statistical package M-plus (v. 7) using a 2-1-2 multilevel approach for mediation analysis. Findings: Generally, branch managers actively implement HPWS, and employees perceive a fairly high level of HPWS. Further, the path model indicated that CHC at the unit level and perceived HPWS at the employee level partially mediate the relationship between implemented HPWS and unit performance. Originality/value: This study is the first to explore multilevel mediating mechanisms in the context of the largest four state-owned banks in China. A 2-1-2 multilevel analysis procedure was used to separate measurement error into relevant employee- and branch-level components to create more precise assessments of multivariate associations. Such analyses have not yet been conducted in research on HPWS prior to this study of the Chinese banking sector, but they are essential for teasing out the micro- and macro-level effects of HPWS.